PENGARUH PENGGABUNGAN TIGA BANK SYARIAH BUMN TERHADAP PERTUMBUHAN DAN STABILITAS INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Ashilah, Nyimas Anindya Raisa; Baidhowi Baidhowi (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Islamic banks emerge as an alternative financial system that is free from usury and operates based on Sharia principles. However, the Islamic banking industry in Indonesia still faces challenges in terms of competitiveness and efficiency. To address these challenges, the government through the Ministry of State-Owned Enterprises BUMN merged three state-owned Islamic banks, namely Bank Syariah Mandiri, BNI Syariah, and BRI Syariah into Bank Syariah Indonesia BSI in 2021. The unification process required time and the right strategy to integrate three banks with different work cultures, operational systems, and policies. This integration affects the growth and stability of the Islamic banking industry in Indonesia. This study employs a qualitative method with a descriptive approach. Data were obtained through a literature review of legislation, academic journals, and relevant scientific articles. As a strategic step, this merger is expected to strengthen Islamic banking to become more competitive both nationally and globally. Continuous innovation and capital structure reinforcement are necessary to support the growth of a Sharia-based economy.